2006
DOI: 10.1186/cc4901
|View full text |Cite
|
Sign up to set email alerts
|

Small volume of hypertonic saline as the initial fluid replacement in experimental hypodynamic sepsis

Abstract: Introduction We conducted the present study to examine the effects of hypertonic saline solution (7.5%) on cardiovascular function and splanchnic perfusion in experimental sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…An explanation could be the larger amount of sodium, which regulated extracellular volume, in the hypertonic groups. This is in good agreement with data from the literature [ 28 , 29 ]. Potential advantages of hypertonic fluid administration rather than isotonic solutions have already been described in shock [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…An explanation could be the larger amount of sodium, which regulated extracellular volume, in the hypertonic groups. This is in good agreement with data from the literature [ 28 , 29 ]. Potential advantages of hypertonic fluid administration rather than isotonic solutions have already been described in shock [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, hypertonic saline in dextran improved the hemodynamics of sepsis patients more effectively than an equivalent volume of normal saline [ 5 - 7 ]. Experimental studies in severe sepsis have also shown beneficial effects [ 8 - 11 ]. In rabbits with septic shock, 5 ml/kg hypertonic (3.5%) saline without colloid induced a decline in cardiac contractility and a decrease in mean arterial pressure (MAP), and eventually resulted in the death of the animals [ 12 ]; whereas in macaque models, the same fluid resuscitation improved myocardial performance [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(11) The weight reduction for CG was larger than for HSG, as CG had no volume replacement, showing that one of the most important, if not the most important benefit, of hypertonic saline solution is quick intracellular compartment fluids mobilization into the extracellular space, endothelial and tissue edema reduction, without large volumes infusion requirement. (10,11) Considering respiratory rate results, all groups had increases, although not statistically significant, thus failing to show the RR improvements reported by Garrido et al (14) and Friedman et al (11) in a review article, which would characterize improved oxygen extraction. However, in an eventual future study more detailed oxymetry could be interesting.…”
Section: Discussionmentioning
confidence: 88%
“…Much was discovered on sepsis' pathophysiology, (13) therefore improving therapeutic perspectives. However, some topics remain unclear, (14) among them hypertonic saline solution volume replacement therapy. (11) Aiming to evaluate the literature-described hemodynamic benefits of hypertonic saline solution therapy in sepsis, this study compared volume replacement using hypertonic 7.5% saline solution versus isotonic 0.9% saline solution in cecum ligation and puncture septic rats, using a control non-intervention septic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation